Pengaruh Kombinasi Pengencer Susu Kacang Kedelai Sangrai dan Sitrat Modifikasi terhadap Kualitas Spermatozoa Babi Landrace - Loka, Kristina; Nalley, W. Marlene; Kune, Petrus (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this study was to evaluate the effect of the combination of roasted soy milk (RSM) diluent and and modified citrate (C) diluent on the quality of landrace boar spermatozoa. The material used in this study was fresh semen of 2-year-old male landrace pigs. This study used a complete randomized design method consisting of 5 treatments and 5 repeats. The treatment was, T0: roasted soybean milk (RSM) 100% + citrate (C) 0%, T1: RSM 75% + C 25%, T2: RSM 50% + C 50%, T3: RSM 25% + C 75% and T4: RSM 0% + C 100%. Diluted semen was stored at 18-20°C and evaluated every 8 hours. The parameters studied are motility, viability, abnormalities and survival of spermatozoa. The data obtained were analyzed using analysis of variance and followed by Duncan’s test. The results showed that T3 significantly differed (P<0,05) on motility, viability and liveability, but not significantly different (P>0,05) on spermatozoa abnormalities. The quality of spermatozoa in T3 treatment was 45.80±1.30% motility, 54.27±4.71% viability, 6.26±0.47% abnormality and 40.00±0.00 hours survival. It can be concluded that the combination of roasted soy milk diluent (RSM) 25% + citrate (C) 75% was an effective treatment in maintaining the quality of landrace boars spermatozoa for 40 hours of storage.